Fermentation of white grape pomace by S. bombicola for the production of sophorolipids - Matos, Rui Pedro Cordes Bento Coelho de (2020)
The use/valorization agro-industrial waste is a priority worldwide. The objective of this work was a novel valorization of white grape pomace (WGP), a lignocellulosic waste feed-stock rich in carbohydrates (around 42 wt. % of free soluble sugars) and oil (around 13 wt. %). The objective was to use the WGP free sugars and oil as carbon sources for the production of sophorolipids (SL) by Starmerella bombicola, a yeast species known for thriving in sugar-rich environments and being fructophilic, while equally comfortable with the presence of oils in growth medium. The goal was to produce sophorolipids (SL), bio-surfactants known to be biodegradable, biocompatible and with high added value surfactant characteristics, which also exhibit anti-tumor and antimicrobial activity. Free sugars of WGP were obtained by water extraction and oils of WGP was obtained by supercritical CO2 extraction and also by Soxhlet extraction. Yeast growth experiments led to a maximum sophorolipid yield of 34.9 g/L with a medium containing both WGP free carbohydrates and oil. Sophorolipids were purified by n-hexane extraction and characterized using LC-MS, 1H-NMR and surface tension. Both types of sophorolipids, lactonic and acidic, with both linoleic acid and oleic acid moieties, were detected in LC-MS analysis. These moieties were the most abundant in WGP oil: linoleic acid (62 %) and oleic acid (17 %). 1H-NMR also detected the presence of C18 hydrocarbon chain lengths and sophorose. The SL obtained had a minimum surface tension (MST) of 35.62 mN/m for a critical micellar concentration (CMC) of 53.79 mg/L.